Prognostisering av sortimentsutfall från stående skog med hjälp av befintliga data - Eriksson, Mikael (SLU/Dept. of Forest Resource Management, 2010)

(untitled)
This study in the subject of forest planning is made for Sveaskog and its aim is to develop tools that prognosticate outcome in terms of volumes per sort from not yet cut forest stands. The degree of detail is just to get reliable results for at least one months volumes, for Sveaskogs own forestland in the market region of Norrbotten that is about 100 000 m3fub. The course of action to accomplish this is regression analysis and the data consists of cut tracts on own forestland in Norrbotten during the years 2006, 2007 and 2008. That is a little more than 4 million m3fub.